2015
DOI: 10.1188/15.cjon.19-06ap
|View full text |Cite
|
Sign up to set email alerts
|

Needs and Lifestyle Challenges of Adolescents and Young Adults With Cancer: Summary of an Institute of Medicine and Livestrong Foundation Workshop

Abstract: Background Among adolescents and young adults (AYAs) in the United States, cancer is the leading cause of disease-related death. AYA survivors face numerous short- and long-term health and psychosocial issues, as well as increased risk for behavioral and lifestyle challenges, including poor diet, low physical activity (PA), and substance abuse. Many of these behaviors are modifiable, but gaps in care serve as barriers for AYA survivors. Objectives The purpose of this article is to (a) raise awareness of AYAs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 56 publications
0
32
0
1
Order By: Relevance
“…The primary aim of this study was to compare the health behaviours of young people with cancer to general population controls. Our results indicate that, despite the importance of health behaviour in cancer survivorship [27][28][29], young people with cancer in the UK have a similar health behaviour status to their peers in that they are largely inactive, consume diets low in fibre, lean meat and fruit and vegetables and regularly binge on alcohol. Nevertheless, reassuringly, a high proportion of TYA cancer patients and survivors held a desire to make positive lifestyle changes, specifically to be more active and have a healthier diet.…”
Section: Discussionmentioning
confidence: 73%
“…The primary aim of this study was to compare the health behaviours of young people with cancer to general population controls. Our results indicate that, despite the importance of health behaviour in cancer survivorship [27][28][29], young people with cancer in the UK have a similar health behaviour status to their peers in that they are largely inactive, consume diets low in fibre, lean meat and fruit and vegetables and regularly binge on alcohol. Nevertheless, reassuringly, a high proportion of TYA cancer patients and survivors held a desire to make positive lifestyle changes, specifically to be more active and have a healthier diet.…”
Section: Discussionmentioning
confidence: 73%
“…TYA health professionals may perceive low levels of patient enquiry about lifestyle as a lack of interest. However, a recent roundtable workshop addressing the needs and the lifestyle challenges of TYA cancer survivors concluded that health professionals working with TYA cancer patients can and should initiate discussions regarding lifestyle behaviour [8].…”
Section: Discussionmentioning
confidence: 99%
“…Given that lifestyle habits formed during adolescence and young adulthood often continue throughout the life-course, it is vital to provide young people who have had a cancer diagnosis are provided with the support necessary to make informed choices about their health behaviour. Health professionals who work with TYA cancer survivors and/or TYA aged childhood cancer survivors are well positioned to provide young people living with and beyond cancer with the right support and guidance to make healthy lifestyle choices [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unique to AYAs is that cancer diagnosis occurs during a developmental stage characterized by the transition from adolescence to adulthood, coinciding with significant developmental milestones such as living independently, entering the workforce, and establishing committed relationships . This transition period often coincides with the initiation of risky health behaviors, such as substance use and a more sedentary lifestyle, and the emergence of affective disturbance …”
Section: Introductionmentioning
confidence: 99%